5HT expression in the stomach and duodenum of the Rhesus Monkey (Macaca mulatta). (August 2020) - de Luca, B.G.; Bastos, A.L.; da S. Souza, A.S.F.; Abidu-Figueiredo, M.; Machado-Santos, C.
Highlights: In the stomach of Rhesus, it was possible to histologically distinguish four regions: cardia, fundus, corpus, and pylorus. The highest frequency of 5-HT cells was observed in the cardia region The 5-HT cells prevailed in gastric glands Rhesus and presented different morphologies. Abstract: This study aims to provide a histological description of different regions of the gastric and duodenal mucosa in Rhesus monkey, as well as to analyze the distribution and the relative frequency of 5-HT. The cardia region mucosa consists of simple columnar epithelium PAS + and AB + and the 5-HT cells were observed at the base of the gland (QA [5-HT cells]/mm²) = 8.72 ± 4.98). The body region, has a smaller number of glands. The 5-HT cells were found predominant in the base of the gastric glands. QA= 6.96 ± 3.81. When compared to body region, the stomach fundus has smaller gastric pits. The 5-HT cells are found at the base of the glands near the main cells. QA = 5.29 ± 2.09. The pylorus region was found to have deep pits and well-developed gastric glands. The 5-HT cells are scarce, at the base of the pyloric gland. QA = 1.18 ± 1.36. The duodenum presented goblet cells strong PAS + and AB +. 5-HT cells were found both in the lining epithelium and in the intestinal glands. QA = 8.16 ± 2.59.